The Success of the Whistleblowing System in Preventing Corruption in the Village Financial Management in Indonesia - Marta, Dwi Jati; Rake, Piers (Inspektorat Kabupaten Majalengka, 2025)
The phenomenon of village fund corruption in Indonesia shows an alarming trend, making villages a new locus of budget mismanagement. Although previous studies have highlighted the importance of transparency and accountability, research on the effectiveness of the Whistleblowing System (WBS) at the village level remains limited and presents inconsistent findings. This study formulates problems concerning the role and effectiveness of the whistleblowing system in preventing village fund corruption, the supporting factors for its success, and the obstacles to its implementation. Using a descriptive qualitative method based on literature studies from regulations, institutional reports, scientific journals, and online news, the data were analyzed through content analysis with source triangulation. The findings indicate that the success of whistleblowing system is determined by the synergy of structural, individual, social, and regulatory factors, while the main obstacles include weak legal protection, cultural patronage, low legal and technological literacy, and the lack of incentives for whistleblowers. This study recommends strengthening the legal framework, digitizing secure reporting channels, and providing incentives for whistleblowers to reinforce clean and accountable village governance.